Pembuatan Game Puzzle Online Dengan Prinsip Kooperatif Berbasis Android - Tofan Bimantara; Sri Dianing Asri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
The growth of online s in Indonesia is fast and is in great demand by many people from children to adults. Online s are very popular because of the PVP system (player vs. player) that let players can fight each other online. PVP s make their customers more competitive and makes players to play more intensively in order to get a higher level or ranking than other player. Playing intensively has an effect on the aggressiveness of players so that behavior makes it less respectful to other player such as issuing invective words to other players. Online s also have systems that are not suitable for kids such as microtransaction and gacha systems. this resulted in kids making transactions without the knowledge of their parents even spending up to tens millions rupiah. not to mention the gacha system, which is the purchase of items at. therefore the author wants to build a application with cooperative principles as a that deserves to be played by kids. In making this Astan Eva application using the MDLC method (Multimedia Development Life Cycle). MDLC has stages by Concept, Design, Material Collecting, Assembly, Testing, and Distribution.